Preliminary Pharmacological Screening of Citrullus colocynthis Linn. Fruits Extracts Using Dextran Sodium Sulfate Induced Colitis in Experimental Animals - Deependra Singh Dangi; Santram Lodhi (Scholars International Journal of Traditional and Complementary Medicine, 2026)
The objective of present study was study of preliminary pharmacological screening of Citrullus colocynthis fruits extracts for ulcerative colitis using Dextran Sodium Sulfate (DSS)-induced colitis in experimental animal. Different extracts i.e. petroleum ether, chloroform, ethyl acetate, ethanol and aqueous extracts of Citrullus colocynthis Linn. fruits were screened for protective effect in Dextran Sodium Sulfate (DSS)-induced colitis through assessment of disease activity index (DAI), myeloperoxidase (MPO) and malondialdehyde (MDA) levels and antioxidants assay in colonic tissues. Results of study were showed that Citrullus colocynthis Linn. give positive test of steroids in petroleum ether and alkaloids in chloroform extract. The ethyl acetate and ethanol extract contains flavonoids, tannins, glycosides and amino acids. Aqueous extract was found presence of carbohydrates, saponins and amino acids. The disease activity index and colon weight were observed significantly decreased after treatment with ethanol extract of Citrullus colocynthis (EECC). Other extracts of Citrullus colocynthis fruits e.g. CECC, EACC and AECC at the dose of 200 mg/kg were does not showed significant Disease activity Index as well as % protection. Treatment with EECC significantly reduced MPO to 12.54 ± 0.12 and MDA to 44.20 ± 1.64 (P<0.05), bringing the values close to normal and comparable to sulfasalazine (MPO: 15.34 ± 0.54; MDA: 45.02 ± 1.73). EECC produced significant improvement in all measured parameters, demonstrating strong anti-inflammatory and antioxidant activities comparable to the standard drug sulfasalazine. This pharmacological screening of different extracts of Citrullus colocynthis fruits suggests that ethanol extract mitigates colonic damage through antioxidant replenishment, reduction of myeloperoxidase (MPO) and malondialdehyde (MDA) levels, and mitigating oxidative stress. Among the tested doses, 200 mg/kg of different extracts, the ethanol extract of Citrullus colocynthis Linn. fruits produced the most pronounced effects and demonstrated efficacy comparable to the standard drug sulfasalazine.